2015
DOI: 10.1002/term.2090
|View full text |Cite
|
Sign up to set email alerts
|

Fibronectin stimulates the osteogenic differentiation of murine embryonic stem cells

Abstract: Conditioned medium from human hepatocarcinoma cells (HepG2-CM) has been shown to stimulate the osteogenic/chondrogenic differentiation of murine embryonic stem cells (mESCs). HepG2-CM is considered to contain visceral endoderm (VE)-like signals and attempts have recently been made to characterize it, using proteomic profiling, with fibronectin being identified as one promising candidate. Herein, we investigated whether fibronectin is able to mimic the activities of HepG2-CM during the osteogenic differentiatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 70 publications
1
32
0
Order By: Relevance
“…These results suggest that COL is a suitable cell expansion matrix to retain high osteogenic differentiation potential of MSC and provide a synergistic effect in promoting osteogenic differentiation in the presence of induction factors prior to in vivo administration. Similar increase in osteogenic differentiation on COL surface was also reported by Linsley et al and others [ 21 , 22 , 24 26 , 28 , 47 ]. Although chondrogenic differentiation is an important property of MSC, it was not tested in the current study as chondrogenic differentiation in vitro is usually performed as a pellet culture where there was no scope for cell to cell-culture-surface contact.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…These results suggest that COL is a suitable cell expansion matrix to retain high osteogenic differentiation potential of MSC and provide a synergistic effect in promoting osteogenic differentiation in the presence of induction factors prior to in vivo administration. Similar increase in osteogenic differentiation on COL surface was also reported by Linsley et al and others [ 21 , 22 , 24 26 , 28 , 47 ]. Although chondrogenic differentiation is an important property of MSC, it was not tested in the current study as chondrogenic differentiation in vitro is usually performed as a pellet culture where there was no scope for cell to cell-culture-surface contact.…”
Section: Discussionsupporting
confidence: 88%
“…Although the matrix rigidity and elasticity were not tested in our study, the results show that differential mechano-sensing and signaling was promoted in cells cultured on different matrices. Even though other studies have shown the usefulness of COL and FBN as suitable extracellular matrix for osteogenic differentiation of MSC [ 21 , 22 , 24 26 , 28 , 47 ], our study specifies their suitability in enhancing cell attachment, migration, cell survival and maintaining their self-renewal and differentiation potential. Taken together, our results suggest that COL might be employed as a matrix during in vitro cell expansion to maintain their osteogenic differentiation potential and coating in vivo scaffolds for increased cell adhesion, proliferation, survival during stress conditions and migration.…”
Section: Discussionmentioning
confidence: 85%
“…Efficient bone tissue engineering strategies require the combination of bioactive materials carrying extracellular matrix (ECM) cues with stem cells (Reddi, ). ECM has been used to increase the bioactivity of polymers, such as PU, and to produce biomaterials capable of regulating stem cell proliferation and differentiation via signals such as cell adhesion (Ahmed & Ffrench‐Constant, ; Kang et al, ). ECM peptides can be synthesized on demand under Good Manufacturing Practice (GMP) conditions eliminating infection risks and avoiding potential immune reactions to animal‐derived proteins such as collagen (Hersel, Dahmen, & Kessler, ).…”
Section: Introductionmentioning
confidence: 99%
“…ECM peptides can be synthesized on demand under Good Manufacturing Practice (GMP) conditions eliminating infection risks and avoiding potential immune reactions to animal‐derived proteins such as collagen (Hersel, Dahmen, & Kessler, ). The arginine‐glycine‐aspartic acid (RGD) sequence was initially identified as the adhesion motif of fibronectin but is now known to be present in a wide variety of ECM proteins essential for cell adhesion and differentiation (Kang et al, ; Ruoslahti, ). Biomaterial surface functionalization with peptides, such as RGD, is advantageous compared with ECM proteins due to the fact that bioactive sites of a whole protein may not be available for integrin binding (Pierschbacher & Ruoslahti, ).…”
Section: Introductionmentioning
confidence: 99%
“…Similar to integrin, FN can bind ECM components such as collagen, fibrin, and heparan sulfate proteoglycans ( 13 ). Furthermore, FN plays a major role in cell adhesion, growth, migration, and differentiation, and it is important for wound healing and embryonic development ( 14 16 ). Altered FN expression, degradation, and/or organization have been associated with a number of pathological changes, including fibrosis and cancer ( 17 , 18 ).…”
Section: Introductionmentioning
confidence: 99%